Batasan Kebebasan Berpendapat di Indonesia Perspektif Hak Asasi Manusia - Lisda Ariany; Sandi P Perdana (Jurnal Hukum Lex Generalis, 2024)
This study discusses the restrictions on freedom of expression in Indonesian legislation and the perspective of human rights (HAM). Through the normative legal research method, this study examines these restrictions based on legal principles and international human rights standards. The results of the study indicate that (1) restrictions are permitted, they must meet strict requirements, namely stipulated by law, and proportional. (2) Freedom of expression is a fundamental right protected by various international instruments, such as Article 19 of the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR). In Indonesia, it is regulated in Law of the Republic of Indonesia Number 9 of 1998 concerning Freedom of Expression in Public and Law of the Republic of Indonesia Number 12 of 2005 concerning Ratification of the ICCPR.